Sherlock Holmes : greatest mysteries [videorecording (DVD)]. - Doyle, Arthur Conan, 1859-1930; Howard, Ronald, 1918-1996; Marion-Crawford, Howard, 1914-1969; Wontner, Arthur, 1875-1960; Rathbone, Basil, 1892-1967; Owen, Reginald, 1887-1972; Lee, Christopher, 1922-2015 (Mill Creek Entertainment, 2009)
Includes : The Sign of Four ; The Triumph of Sherlock Holmes ; Murder at the Baskervilles ; The Woman in Green ; A Study in Scarlet ; Sherlock Holmes and the Secret Weapon ; Terror by Night ; and Dressed to Kill.